School Organizational Culture and Leadership: Theoretical Trends and New Analytical Proposals - Leonor L. Torres (MDPI AG, 2022)
Various changes in the spheres of education policy and school management over recent decades have sparked a renewed interest in the issue of school culture and its potential to understand processes of leadership and academic performance. What are the contributions and potentialities of organizational culture for understanding school organizations and their leadership processes? This article has two goals: (i) to identify trends and theoretical particularities inherent to the major approaches to organizational culture, focusing on research carried out in the school setting; (ii) to debate the heuristic usefulness of a theoretical proposal for studying organizational culture in the school setting. The article presents a multidimensional analysis of school organizational culture, considering political, social and educational factors, aiming to capture the unique nature of school cultures and their links to processes of leadership and management. By linking these to different leadership perspectives, this model may inspire further comparative study of educational management in an international context. This approach demonstrates the need to tailor models for analysing organizational culture to the school environment, to achieve a deeper and more solid understanding of school life and leadership and management phenomena.